Powering State Islamic Universities Management with Balanced Scorecard Insight - Rukiah Rukiah; Ananda Anugrah Nasution; Wanda Khairun Nasirin (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study examines the relationship between the implementation of GUG, organizational culture, internal control, and management performance at State Islamic Religious Universities (PTKIN) in North Sumatra, with organizational commitment as a moderating variable. This research is a quantitative associative study conducted in 2023, focusing on PTKIN in North Sumatra Province. The research population consists of all program study leaders at State Islamic Religious Universities in North Sumatra. Data analysis was conducted using PLS SEM with the Smart PLS application. The research results indicate that Good University Governance (GUG) has a significant influence on management performance at PTKIN. Additionally, a strong organizational culture and effective internal control also positively contribute to management performance at PTKIN. Organizational commitment does not significantly affect management performance at PTKIN and does not moderate the influence of factors such as GUG, Organizational Culture, and Internal Control. This suggests that despite implementing GUG, a strong organizational culture, and an internal control system, organizational commitment does not significantly impact the strengthening of PTKIN management performance in North Sumatra. This research also indicates that management performance, measured by the Balanced Scorecard (BSC), is highly correlated with the integration of tawhid, such as financial performance being related to ihsan and israf, internal process performance being related to the principles of itqan and amanah, learning and growth performance being closely related to Tafaqquh fi 'l-Din and Ilm, and customer performance being related to Adl and Maslahah.